Analisis Kualitas Terjemahan dari Bahasa Inggris ke dalam Bahasa Indonesia - Titis Surgawi; Hermanu Joebagio; Djono Djono (Universitas Sebelas Maret, 2018)
Language is an important way of communicating with the people. Sometimes, the people in another place may feel difficult to understand what the meaning when they are talking with others. The way to catch and understand meaning is by translating it. Translation is the process of moving meaning from one language into another language. This research aims to explain the quality of translation of Garuda Magazine from English into Indonesian. The analysis concern on accuracy, clarity/clearness and naturalness of translation of Garuda Magazine from English into Indonesian. The research method uses qualitative descriptive and the type of research is content analysis. This research takes the segment “Welcome on Board” page 12 on Garuda Magazine in term November 2008 as source of data. The result of the research shows that 3 data (15,79 %) are less accurate translation and 84, 21% or 16 sentences out of 19 sentences are accurate; 3 data (15,79 %) are less clear translation and 84, 21% or 16 sentences out of 19 sentences are clear; 5, 26 % or 1 sentence out of 19 sentences is unnatural, 36, 84 % or 7 sentences out of 19 sentences are less natural and 57, 90 % or 11 sentences out of 19 sentences are natural